2020
DOI: 10.3390/genes11121499
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses Reveal Differential Transcriptional Profiles in Early- and Late-Dividing Porcine Somatic Cell Nuclear Transfer Embryos

Abstract: Somatic cell nuclear transfer (SCNT) is not only a valuable tool for understanding nuclear reprogramming, but it also facilitates the generation of genetically modified animals. However, the development of SCNT embryos has remained an uncontrollable process. It was reported that the SCNT embryos that complete the first cell division sooner are more likely to develop to the blastocyst stage, suggesting their better developmental competence. Therefore, to better understand the underlying molecular mechanisms, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…It is uncertain whether DNA damage causes protein misfolding in the ER. It has been reported that 1896 DEGs were identified between SCNT early cleavage embryos and late cleavage embryos [ 19 ]. Similar results to ours showed that the DEGs were enriched in the ribosome, mRNA surveillance, protein processing in the endoplasmic reticulum, and spliceosome pathways [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain whether DNA damage causes protein misfolding in the ER. It has been reported that 1896 DEGs were identified between SCNT early cleavage embryos and late cleavage embryos [ 19 ]. Similar results to ours showed that the DEGs were enriched in the ribosome, mRNA surveillance, protein processing in the endoplasmic reticulum, and spliceosome pathways [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse studies have found that relatively early cleavage embryos relation to better developmental competence than those cleaving later embryos in pig [ 11 , 12 ], human [ 13 ], buffalo [ 14 ], cattle [ 7 , 15 ], goat [ 16 ], hamster [ 17 ], and mouse [ 18 ]. It has been reported that early cleavage embryos exhibited higher expression in genes that participated in the meiotic cell cycle, while enrichment of RNA processing- and translation-related genes was found in porcine late cleavage embryos of somatic cell nuclear transfer (SCNT) [ 19 ]. While the delay of cell division might be a consequence of chromosomal aberrations and DNA damage [ 20 ], slow cleaving embryos have a higher caspase activity in comparison to fast cleavers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Liu et al (2020) found that overexpression of Kdm5b , an H3K4me3 demethylase, rescued 4-cell arrest in mouse cloned embryos. Moreover, the combination of K4m4b and Kdm5b improved the SCNT blastocyst rate to over 95%, and 11.1% of reconstructed embryos developed to full term.…”
Section: Strategies To Overcome Epigenetic Barriersmentioning
confidence: 99%
“…The efficiency of SCNT-based cloning in mammals remains at relatively or extremely low levels, and it appears to differ in a species-specific manner. To improve the SCNT efficiency, extensive efforts are needed to precisely identify the epigenetic factors and molecular mechanisms involved in the reprogramming of the nuclear donor cell’s (NDC’s) genome in somatic cell cloned embryos ( Cao et al, 2020 ; Liu et al, 2020 ; Feng et al, 2022 ; Li et al, 2022 ). Thus far, the provenance and type of NDCs have been shown to influence the capability of donor genomic DNA to be epigenetically reprogrammed in the oocyte cytoplasm during SCNT ( Samiec and Skrzyszowska, 2010 , 2013 ; Sadeesh et al, 2016 ; Wiater et al, 2021b ; Xu et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proper reprogramming to totipotency in SCNT embryos can be hampered by both lack of gene activation and failure to inactivate the transcriptional memory of somatic nuclei following nuclear transfer ( Ng and Gurdon, 2005 ; Matoba et al, 2014 ). The transcriptional memory of somatic cells was more efficiently reprogrammed in SCNT embryos that cleaved early and produced higher blastocyst rates than late cleaving embryos ( Liu et al, 2020 ). In addition, attenuation of the transcriptional memory for 15 h after nuclear transfer, using the inhibitor of RNA polymerase II, 5,6-Dichlorobenzimidazole 1-β- d -ribofuranoside (DRB), improved gene expression in bovine SCNT embryos and increased blastocyst cell numbers ( Rissi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%